Políticas de inclusión en educación superior. El programa nacional BECA 18 - Rodríguez González, Yolanda (2020)
Higher education systems in Latin America experienced remarkable growth since the middle of the last century. In the 1990s, in line with neoliberal reforms, the pressure for access to this educational level was responded to through policies of deregulation of education promoting the expansion of the private sector. Peru is not an exception to this process. Despite this experienced growth, the regional average of the higher education enrollment rate is low with large differences between the countries of the region. This panorama of inequity has given rise in different countries of the region since the late 1990s, to the implementation of compensatory policies such as scholarships and educational loans for young people from poor and / or marginalized social groups due to their social or ethnic origin. This article addresses the subsidy system through PRONABEC that has recently been implemented in Peru.